2016
DOI: 10.1002/cbf.3189
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma‐derived growth factor promotes growth and metastasis of hepatocellular carcinoma cells

Abstract: We aimed to elucidate the effects of hepatoma-derived growth factor (HDGF) on growth and metastasis of hepatocellular carcinoma (HCC) cells. Tissue microarrays with 236 HCC specimens and 18 extrahepatic metastases were utilized to detect the HDGF expression by immunohistochemistry. Meanwhile, HDGF expressions in HCC cell lines with different metastatic potentials were examined using immunofluorescence staining, real-time PCR and western blotting. After HDGF silencing, the growth and metastatic potentials of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…HDGF is suggested to be related to lipogenesis, and the change in the lipid metabolism may contribute to the mitosis of hepatoma cells. [2,3,16,19,[32][33][34][35][36][37] Pancreatic cancer…”
Section: Malignant Digestive System Diseases Main Findings Reference(s)mentioning
confidence: 99%
See 3 more Smart Citations
“…HDGF is suggested to be related to lipogenesis, and the change in the lipid metabolism may contribute to the mitosis of hepatoma cells. [2,3,16,19,[32][33][34][35][36][37] Pancreatic cancer…”
Section: Malignant Digestive System Diseases Main Findings Reference(s)mentioning
confidence: 99%
“…As HDGF was originally identified as a growth factor for hepatoma cells, various studies have demonstrated that HDGF is associated with the progression of HCC [32][33][34][35][36][37]. The expression of HDGF was detected in several hepatoma-derived cell lines [2,3].…”
Section: Hdgf In Hepatocellular Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Two other chromosome contacts with PEAR1 involve two genes whose abnormal expression is reported to lead to growth of several tumours [ 66 , 67 , 68 , 69 , 70 ]. PRCC is involved in mRNA splicing and reported to have a role in cell cycle delay.…”
Section: Discussionmentioning
confidence: 99%